Dynamic Analysis of Nonlinear Impulsive Neutral Nonautonomous Differential Equations with Delays - Jinxian Li (Abstract and Applied Analysis)
A class of neural networks described by nonlinear impulsive neutral nonautonomous differential equations with delays is considered. By means of Lyapunov functionals and differential inequality technique, criteria on global exponential stability of this model are derived. Many adjustable parameters are introduced in criteria to provide flexibility for the design and analysis of the system. The results of this paper are new and they supplement previously known results. An example is given to illustrate the results.